Financial Profitability of Carbon Offset Monoculture Plantation Forestry on Smallholder Farms in Trans Mara Sub-County, Kenya. Issue 1 (5th July 2019) - Chemuliti, J.; Ackello-Ogutu, C.; Mbogoh, S.; Irungu, P.
ABSTRACT: There is growing interest in the development of smallholder carbon offset forestry projects in Africa as a means of mitigating climate change while providing co-benefits of development and environmental protection and conservation. Financial profitability of carbon projects is a key determinant that could influence smallholder farmers' willingness to participate in them. However, current knowledge has not elucidated fully whether these projects, particularly those based on exotic monoculture forestry systems, are financially profitable for smallholder farmers in Africa. This paper reports on the results of a study conducted in Trans Mara sub-County in Kenya to assess the potential financial profitability of smallholder carbon offset Eucalyptus spp. plantation forestry and compare its nett returns with existing agricultural enterprises. Data was collected from 206 farmers using semi-structured questionnaires and analyzed using discounted cash flow techniques and partial budget method. The results showed that a carbon enterprise for multiple objectives of construction poles and carbon was profitable financially and more profitable than maize and bean enterprises. A carbon sequestration only enterprise was unprofitable. It was concluded that a carbon offset Eucalyptus spp. enterprise can be a source of income to farmers especially those with underutilized or marginal agricultural lands or those seeking opportunities to diversify their farming enterprises.